Adsorption Of Methylene Blue Using Chitosan Membrane Embedded With Multi-Walled Carbon Nanotubes - Alias, Jahira (Universiti Sains Malaysia, 2018)
In this study, the chitosan (CS) and CS embedded with multi-walled carbon nanotubes (CS/MWCNTs) membrane were synthesized using solution casting method. The resultant membranes were used to study the adsorption of methylene blue (MB) in terms of contact time, initial MB concentration and temperature. The effect of contact time was conducted from 60-240 minutes at temperature of 25°C and MB concentration 4 mg/L. For study of the effect of MB concentration, different dye concentrations ranging from 1 mg/L to 4 mg/L at were conducted while the temperature and the contact time was maintained at 25 °C and 240 minutes, respectively. The effect of temperature was studied from 25°C to 40°C at MB concentration at 4 mg/L and time 240 minutes. Adsorption test showed that the CS/MWCNTs showed higher adsorption capacity and removal efficiency of MB than CS membrane without MWCNTs. The maximum adsorption capacity and removal efficiency were found to be 0.0160 mg/g and 93.8% and 0.0019 mg/g and 12.5% for CS/MWCNTs and CS membrane without MWCNTs, respectively at conditions temperature 40°C, contact time 240 minutes and MB concentration 4 mg/L. The equilibrium isotherm was analysed using Langmuir and Freundlich model. Adsorption for MB follows Freundlich model. Kinetic analysis was conducted using pseudo-first order and second order. The results showed the adsorption of MB fitted well for pseudo-second order.